The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1186/1475-2859-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sugar binding proteins and binders of intermediate sugar metabolites derived from microbes are increasingly being used as reagents in new and expanding areas of biotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Finally, the information contained in the MD simulations will be used to address some unresolved issues in the experimental PEPCK literature, including the role of an active site lid in achieving optimal enzymatic efficiency . Overall, the results of this work will offer guidance to future efforts designing bioinspired CO 2 capture and sequestration systems …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the information contained in the MD simulations will be used to address some unresolved issues in the experimental PEPCK literature, including the role of an active site lid in achieving optimal enzymatic efficiency . Overall, the results of this work will offer guidance to future efforts designing bioinspired CO 2 capture and sequestration systems …”
Section: Introductionmentioning
confidence: 98%
“…26 Overall, the results of this work will offer guidance to future efforts designing bioinspired CO 2 capture and sequestration systems. 38 2. COMPUTATIONAL METHODS 2.1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, N 2 is fixed by bacterial nitrogenases, O 2 and CO 2 are transported in the blood by hemoglobin, NO controls vasodilation, and CO 2 is fixed in the Calvin cycle by the enzyme RuBisCO . This last, the enzymatic utilization of carbon dioxide, not only represents the ultimate energy source for all higher life, but has also recently been scrutinized in the context of developing biotechnological approaches to ameliorate rising levels of atmospheric CO 2 . Recent research detailing protein–CO 2 interactions has revealed patterns in primary, secondary, and tertiary protein structure that influence carbon dioxide binding affinity.…”
mentioning
confidence: 99%